Pemanfaatan Pewarna Alami dari Kulit Kayu Tingi dengan Teknik Ecoprint pada Kain Katun - Nisa, Atina Khoiron; Nafi’ah, Nayla Fikriatun (BAJU: Journal of Fashion and Textile Design Unesa, 2025)
The bark of the tingi tree (Ceriops tagal), a mangrove species commonly found in coastal regions, serves as a natural source of brown pigment capable of imparting appealing coloration to textiles. However, the utilization of tingi bark as a natural dye through ecoprint techniques remains relatively underexplored. This study employed an experimental approach comprising several stages: extraction, premordanting, dyeing, ecoprinting, and fixation. The leaf-based ecoprint process revealed that teak leaves produced a reddish-purple hue, while guava, castor, cassava, and fern leaves yielded lighter, whitish tones. The final outcomes demonstrate that fabrics dyed with tingi bark using ecoprint methods. There was a loss of fabric mass during washing with 1% detergent, indicating that the dye and mordant had not fully adhered to the fabric.